Probable sarcopenia and sarcopenia among older adults treated at a teaching clinic (Revista Científica Integrada, 2024)
Objective: To estimate the prevalence, incidence, and factors associated with probable sarcopenia and sarcopenia among elderly individuals attending a clinical school. Method: Prospective longitudinal study conducted from August 2016 to November 2018. It was divided into two periods: a cross-sectional from August 2016 to November 2018 (n=129), and a prospective follow up period from August 2018 to November 2018 (n=66). The variables probable sarcopenia and sarcopenia were grouped together as the dependent variable. Results: The prevalence and incidence of sarcopenia and probable sarcopenia were 34.1% and 35.7%, respectively. In the multivariate analysis of the cross-sectional study, age, not living with a spouse, and being an ex-smoker were associated with the dependent variable. In the prospective study, the analysis reinforced the association between age, not living with a spouse, and presenting symptoms of gastroesophageal reflux disease. Conclusion: The prevalence and incidence of probable sarcopenia and sarcopenia among the evaluated elderly individuals are considered high, highlighting the need to study the factors associated with this outcome.
Keywords: Sarcopenia; Frailty; Aged; Incidence; Risk Factors